Three-dimensional composite aerogel phase change material and preparation method thereof
By constructing a three-dimensional composite aerogel structure in a phase change material, using graphene skeleton, two-dimensional copper elemental network and polyethylene glycol-grafted honeycomb AlAg@C particles, the problems of insufficient thermal conductivity and polyethylene glycol packaging effect of phase change material are solved, and efficient thermal storage and structural stability are achieved.
Patent Information
- Application Number
- CN202510140116.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to effectively improve the thermal conductivity of phase change materials and the packaging effect of polyethylene glycol, resulting in insufficient thermal storage efficiency and structural stability.
By constructing a three-dimensional composite aerogel material, graphene is used as a skeleton, and a two-dimensional copper elemental network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to it to form a porous structure to improve thermal conductivity and packaging effect.
The thermal conductivity of phase change materials is improved, the packaging effect of polyethylene glycol is enhanced, the thermal storage efficiency and structural stability are improved, and the composite material is given certain sterilization properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of phase change materials, and in particular to a three-dimensional composite aerogel phase change material. Background Art
[0002] As the energy crisis intensifies, environmental pollution and energy waste become more serious, phase change energy storage is the storage and release of energy by absorbing / releasing heat during the phase change process. Phase change energy storage material is a green, energy-saving and environmentally friendly material, and is the key carrier of phase change energy storage technology. It has the advantages of high energy density, constant operating temperature and almost unchanged volume, and is one of the key research objects in the current field of energy storage technology.
[0003] Phase change material refers to a material that can change its physical state within a certain temperature range. It uses the temperature difference between the environment and the system as a driving force to achieve heat storage and release functions, and during the phase change process, the temperature of the material remains almost unchanged. It has the advantages of high energy storage density, strong energy storage capacity, and constant temperature, and has received widespread attention in application fields such as smart temperature-regulating clothing, construction, and electronic devices. The Joule series of composite phase change heat storage materials can not only effectively overcome the shortcomings of single inorganic or organic phase change heat storage materials, but also improve the application effect of phase change materials and expand their application range to meet the needs of specific occasions. At present, composite phase change heat storage materials have been widely used in human life and will become the best green and environmentally friendly carrier for energy conservation and environmental protection. They have been listed as a national-level research and development and utilization sequence in my country.
[0004] Porous encapsulated shaped phase change composite materials are formed by encapsulating phase change materials in pores with porous materials as carriers, and limiting the flow of liquid phase change materials in limited pore space through intermolecular forces and capillary forces between the carrier pores and the phase change materials. According to the different dimensions of the formed pores, they can be divided into one-dimensional pores, two-dimensional pores and three-dimensional pore encapsulated shaped phase change composite materials. The three-dimensional pore structure has become a hot topic in the current research of phase change composite materials due to its large porosity, continuous network and stable mechanical properties. Summary of the invention
[0005] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a three-dimensional composite aerogel phase change material, which can improve the thermal conductivity of the phase change material and effectively encapsulate polyethylene glycol by constructing a porous structure.
[0006] Technical solution: A three-dimensional composite aerogel phase change material. The three-dimensional composite aerogel uses graphene as a skeleton. A two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton.
[0007] Preferably, the preparation method comprises the following steps: S1. dispersing graphene and polyethylene glycol-grafted AlAg@C particles in water to form a suspension with a mass fraction of 25-40wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonicated to obtain a homogeneous mixed solution; S3. freeze-dry the homogeneous mixed solution obtained in S2 at -50 to -30°C for 35 to 45 hours to obtain an initial aerogel; S4. Add the initial aerogel obtained in S3 into a reducing solution with a mass fraction of 30-45wt% to obtain a three-dimensional composite aerogel phase change material.
[0008] Preferably, the mass ratio of graphene to polyethylene glycol-grafted honeycomb AlAg@C particles in S1 is 1:0.3-0.6.
[0009] Preferably, the volume ratio of the suspension in S2, the copper chloride aqueous solution and the polyphenol amine / hydrochloric acid solution is 10-15:3-5:1-2, the mass fraction of the copper chloride aqueous solution is 20-35wt%, and the concentration of the polyphenol amine / hydrochloric acid solution is 2-4g / L.
[0010] Preferably, the concentration of the reducing solution in S4 is 1.5-3.5 g / L, and the reducing solution is one or more of hydrazine hydrate solution, sodium borohydride solution or sodium sulfite solution.
[0011] Preferably, the method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Dispersing aluminum nitrate, silver nitrate and PVA in water to obtain a mixed solution with a mass fraction of 10 to 25 wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70-80° C. for 40-80 min, and then dried to obtain aluminum nitrate silver nitrate@PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 are ball-milled, and then the ball-milled particles are heated at 700-900° C. for 0.5-1.5 h in a nitrogen atmosphere to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2 to 3:1 to water, and heating at 50 to 70° C. for 2 to 4 hours to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained in S14 are added to a polyethylene glycol aqueous solution, and bismuth isooctanoate is added, and the polyethylene glycol-grafted honeycomb AlAg@C particles are obtained after heating for reaction.
[0012] Preferably, the mass ratio of aluminum nitrate, silver nitrate and PVA in S11 is 1-3:1-4:0.3-0.5.
[0013] Preferably, the particle size of the particles after ball milling in S13 is 100-150 μm, and the heating rate of the nitrogen is 3-5° C. / min.
[0014] Preferably, the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol in S15 is 1:15-35, the molecular weight of polyethylene glycol is 2000-8000, the heating reaction temperature is 90-120° C., and the time is 6-10 hours.
[0015] Beneficial effects: 1. The honeycomb AlAg@C particles prepared in the present invention play a supporting role in the aerogel pores, can form tiny pores to provide capillary force, help stabilize the phase change material and reduce the possibility of leakage, and this capillary action helps to distribute and maintain the phase change material in the matrix, thereby improving its heat storage capacity; the honeycomb AlAg@C particles also give the aerogel a layered structure, which can provide gradient thermal protection, thereby improving the heat storage efficiency of the phase change material; in addition, the presence of Ag gives the composite material certain bactericidal properties; 2. The two-dimensional copper network prepared in the present invention can provide an efficient heat conduction path, so that the phase change material can exchange heat faster when absorbing and releasing heat, thereby improving the efficiency of heat energy storage and release; and the two-dimensional copper network can provide a stable skeleton structure to resist the volume change of the material during the phase change process, thereby enhancing the structural stability of the phase change material; 3. The polyphenolamine added in the present invention has an amino group and a phenolic hydroxyl group, which makes it have a strong chelating ability for metal ions and can serve as a "connecting bridge" between the phase change substrate and the two-dimensional copper network; and the polyphenolamine has a mild reducing property, and the copper ions are first absorbed on the polyphenolamine and then reduced to CuNPs in situ. The obtained CuNPs act as seeds to promote the formation of the two-dimensional copper network; 4. In the present invention, polyethylene glycol is grafted onto the honeycomb AlAg@C particles. There is a steric hindrance effect between the long chains of polyethylene glycol, which increases the distance between molecules to avoid the aggregation of particles, thereby improving the dispersion performance of the particles. The well-dispersed nanoparticles can reduce the void space and improve the thermal conductivity of the phase change material. 5. In the present invention, the layered structure constructed by the honeycomb AlAg@C particles, the pores of the two-dimensional copper network and the pore structure of the graphene aerogel together construct a porous structure. The porous structure can provide more channels, so that heat can be transferred more effectively; and the porous structure can provide physical support, reduce the volume expansion and contraction of the phase change material during the phase change process, thereby improving the shape stability; in addition, polyethylene glycol is a long-chain polymer, and the capillary force and surface tension generated by the porous aerogel prevent the leakage of liquid polyethylene glycol through adsorption. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:
[0017] Example 1 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.3 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 10:3:1, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 700° C. for 0.5 h in a nitrogen atmosphere at a heating rate of 3° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:15, and the molecular weight of polyethylene glycol is 2000. Bismuth isooctanoate is added, and the polyethylene glycol-grafted honeycomb AlAg@C particles are obtained after heating at 90°C for 6 hours.
[0018] Example 2 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.6 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 10:3:1, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 700° C. for 0.5 h in a nitrogen atmosphere at a heating rate of 3° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:15, and the molecular weight of polyethylene glycol is 2000. Bismuth isooctanoate is added, and the polyethylene glycol-grafted honeycomb AlAg@C particles are obtained after heating at 90°C for 6 hours.
[0019] Example 3 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.6 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 10:5:2, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 800° C. for 1 h in a nitrogen atmosphere at a heating rate of 5° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2.5:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:20, and the molecular weight of polyethylene glycol is 6000. Bismuth isooctanoate is added, and the mixture is heated at 100°C for 8h to obtain polyethylene glycol-grafted honeycomb AlAg@C particles.
[0020] Example 4 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.6 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 8:5:1, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 800° C. for 1 h in a nitrogen atmosphere at a heating rate of 5° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2.5:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:20, and the molecular weight of polyethylene glycol is 6000. Bismuth isooctanoate is added, and the mixture is heated at 100°C for 8h to obtain polyethylene glycol-grafted honeycomb AlAg@C particles.
[0021] Example 5 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.5 were dispersed in water to form a suspension with a mass fraction of 35wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 12:3:1, the mass fraction of the copper chloride aqueous solution was 30wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 4g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 40h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 35wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:4:0.5 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 800° C. for 0.5 h in a nitrogen atmosphere at a heating rate of 3° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:25, and the molecular weight of polyethylene glycol is 6000. Bismuth isooctanoate is added, and the mixture is heated at 110°C for 6 hours to obtain polyethylene glycol-grafted honeycomb AlAg@C particles.
[0022] Example 6 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.5 were dispersed in water to form a suspension with a mass fraction of 35wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 15:4:2, the mass fraction of the copper chloride aqueous solution was 30wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 3g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 40h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 35wt% sodium borohydride solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 3:2:0.5 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 800° C. for 0.5 h in a nitrogen atmosphere at a heating rate of 4° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:30, and the molecular weight of polyethylene glycol is 7000. Bismuth isooctanoate is added, and the mixture is heated at 110°C for 6 hours to obtain polyethylene glycol-grafted honeycomb AlAg@C particles.
[0023] Example 7 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.5 were dispersed in water to form a suspension with a mass fraction of 40wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 15:4:2, the mass fraction of the copper chloride aqueous solution was 30wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 3g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 40h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 35wt% sodium borohydride solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 3:4:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate and silver nitrate@PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 120 μm, and then the ball-milled particles were heated at 800° C. for 0.5 h in a nitrogen atmosphere at a heating rate of 4° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:35, and the molecular weight of polyethylene glycol is 7000. Bismuth isooctanoate is added, and the mixture is heated at 110°C for 6 hours to obtain polyethylene glycol-grafted honeycomb AlAg@C particles.
[0024] Example 8 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.5 were dispersed in water to form a suspension with a mass fraction of 40wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 15:4:2, the mass fraction of the copper chloride aqueous solution was 30wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 3g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 40h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 35wt% sodium borohydride solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 3:4:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 120 μm, and then the ball-milled particles were heated at 900° C. for 1.5 h in a nitrogen atmosphere at a heating rate of 5° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:35, and the molecular weight of polyethylene glycol is 8000. Bismuth isooctanoate is added, and the mixture is heated at 120°C for 8h to obtain polyethylene glycol-grafted honeycomb AlAg@C particles.
[0025] Comparative Example 1 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.1 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 10:3:1, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 700° C. for 0.5 h in a nitrogen atmosphere at a heating rate of 3° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:15, and the molecular weight of polyethylene glycol is 2000. Bismuth isooctanoate is added, and the polyethylene glycol-grafted honeycomb AlAg@C particles are obtained after heating at 90°C for 6 hours.
[0026] Comparative Example 2 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.8 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 10:3:1, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 700° C. for 0.5 h in a nitrogen atmosphere at a heating rate of 3° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to the polyethylene glycol is 1:15, and the molecular weight of the polyethylene glycol is 2000, and bismuth isooctanoate is added, and the mixture is heated at 90° C. for 6 h to obtain polyethylene glycol-grafted honeycomb AlAg@C particles; Table 1 Effect of the mass ratio of graphene and polyethylene glycol grafted AlAg@C particles on phase change properties
[0027] Comparative Example 3 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.6 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 8:2:0.5, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 800° C. for 1 h in a nitrogen atmosphere at a heating rate of 5° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2.5:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained by S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol is 1:20, and the molecular weight of polyethylene glycol is 6000. Bismuth isooctanoate is added, and the mixture is heated at 100°C for 8h to obtain polyethylene glycol-grafted honeycomb AlAg@C particles.
[0028] Comparative Example 4 A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has a graphene skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.6 were dispersed in water to form a suspension with a mass fraction of 25 wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 16:7:3, the mass fraction of the copper chloride aqueous solution was 20wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 2g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 35h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was added to a 30wt% hydrazine hydrate solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 1:1:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 100 μm, and then the ball-milled particles were heated at 800° C. for 1 h in a nitrogen atmosphere at a heating rate of 5° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2.5:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained in S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to the polyethylene glycol is 1:20, and the molecular weight of the polyethylene glycol is 6000. Bismuth isooctanoate is added, and the mixture is heated at 100° C. for 8 h to obtain polyethylene glycol-grafted honeycomb AlAg@C particles. Table 2 Effect of volume ratio of suspension, copper chloride solution, polyphenolamine / hydrochloric acid solution on phase change properties
[0029] Comparative Example 5 The difference between this comparative example and Example 5 is that the AlAg@C particles do not construct a honeycomb structure.
[0030] Comparative Example 6 The difference between this comparative example and Example 6 is that the polyethylene glycol is not grafted onto the honeycomb-shaped AlAg@C particles, but is directly dissolved in the solution.
[0031] Comparative Example 7 The difference between this comparative example and Example 7 is that no two-dimensional copper single substance network is generated.
[0032] Comparative Example 8 The difference between this comparative example and Example 8 is that a two-dimensional copper single substance network is generated on the surface of the aerogel; A three-dimensional composite aerogel phase change material, wherein the three-dimensional composite aerogel has graphene as a skeleton, and a two-dimensional copper single substance network and polyethylene glycol-grafted honeycomb AlAg@C particles are attached to the surface of the graphene skeleton; Wherein, the preparation method comprises the following steps: S1. Graphene and polyethylene glycol-grafted AlAg@C particles in a mass ratio of 1:0.5 were dispersed in water to form a suspension with a mass fraction of 40wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonically treated in a volume ratio of 15:4:2, the mass fraction of the copper chloride aqueous solution was 30wt%, the concentration of the polyphenolamine / hydrochloric acid solution was 3g / L, and a homogeneous mixed solution was obtained; S3. The homogeneous mixed solution obtained in S2 was freeze-dried at -50°C for 40h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 was immersed in a 30wt% copper chloride aqueous solution, and after drying, the aerogel was added to a 35wt% sodium borohydride solution to obtain a three-dimensional composite aerogel phase change material; The method for preparing the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Aluminum nitrate, silver nitrate and PVA in a mass ratio of 3:4:0.3 were dispersed in water to obtain a mixed solution with a mass fraction of 10wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70° C. for 40 min, and then dried to obtain aluminum nitrate silver nitrate @PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 were ball-milled to obtain particles with a particle size of 120 μm, and then the ball-milled particles were heated at 900° C. for 1.5 h in a nitrogen atmosphere at a heating rate of 5° C. / min to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2:1 to water, and heating at 50° C. for 2 h to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained in S14 are added to a polyethylene glycol aqueous solution, wherein the mass ratio of the oxidized honeycomb AlAg@C particles to the polyethylene glycol is 1:35, and the molecular weight of the polyethylene glycol is 8000. Bismuth isooctanoate is added, and the mixture is heated at 120° C. for 8 h to obtain polyethylene glycol-grafted honeycomb AlAg@C particles. Table 3 Phase change properties of different embodiments and comparative examples
[0033] Note: 1. Thermal conductivity test reference standard "ASTM C1784"; 2. The test reference standard for phase change enthalpy is "ASTM E793-06".
[0034] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A three-dimensional composite aerogel phase change material, characterized in that: The three-dimensional composite aerogel uses graphene as a skeleton, and a two-dimensional copper single substance network and honeycomb AlAg@C particles grafted with polyethylene glycol are attached to the graphene skeleton.
2. The method for preparing a three-dimensional composite aerogel phase change material according to claim 1, characterized in that: The preparation method comprises the following steps: S1. dispersing graphene and polyethylene glycol-grafted AlAg@C particles in water to form a suspension with a mass fraction of 25-40wt%; S2. The suspension obtained in S1, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution were mixed and ultrasonicated to obtain a homogeneous mixed solution; S3. freeze-dry the homogeneous mixed solution obtained in S2 at -50 to -30°C for 35 to 45 hours to obtain an initial aerogel; S4. Add the initial aerogel obtained in S3 into a reducing solution with a mass fraction of 30-45wt% to obtain a three-dimensional composite aerogel phase change material.
3. The method for preparing a three-dimensional composite aerogel phase change material according to claim 2, characterized in that: The mass ratio of graphene to the honeycomb AlAg@C particles grafted with polyethylene glycol in S1 is 1:0.3-0.
6.
4. The method for preparing a three-dimensional composite aerogel phase change material according to claim 2, characterized in that: The volume ratio of the suspension in S2, the copper chloride aqueous solution and the polyphenolamine / hydrochloric acid solution is 10-15:3-5:1-2, the mass fraction of the copper chloride aqueous solution is 20-35wt%, and the concentration of the polyphenolamine / hydrochloric acid solution is 2-4g / L.
5. The method for preparing a three-dimensional composite aerogel phase change material according to claim 2, characterized in that: The concentration of the reducing solution in S4 is 1.5-3.5 g / L, and the reducing solution is one or more of hydrazine hydrate solution, sodium borohydride solution or sodium sulfite solution.
6. The method for preparing the three-dimensional composite aerogel phase change material according to claim 2, characterized in that: The preparation method of the polyethylene glycol-grafted honeycomb AlAg@C particles in S1 comprises the following steps: S11. Dispersing aluminum nitrate, silver nitrate and PVA in water to obtain a mixed solution with a mass fraction of 10 to 25 wt%; S12. The mixed solution obtained in S11 was stirred in a water bath at 70-80° C. for 40-80 min, and then dried to obtain aluminum nitrate silver nitrate@PVA particles; S13. The aluminum nitrate silver nitrate @PVA particles obtained in S12 are ball-milled, and then the ball-milled particles are heated at 700-900° C. for 0.5-1.5 h in a nitrogen atmosphere to obtain honeycomb AlAg@C particles; S14. Adding honeycomb AlAg@C particles and fumaric acid in a mass ratio of 2 to 3:1 to water, and heating at 50 to 70° C. for 2 to 4 hours to obtain oxidized honeycomb AlAg@C particles; S15. The oxidized honeycomb AlAg@C particles obtained in S14 are added to a polyethylene glycol aqueous solution, and bismuth isooctanoate is added, and the polyethylene glycol-grafted honeycomb AlAg@C particles are obtained after heating for reaction.
7. The method for preparing a three-dimensional composite aerogel phase change material according to claim 6, characterized in that: The mass ratio of aluminum nitrate, silver nitrate and PVA in S11 is 1-3:1-4:0.3-0.
5.
8. The method for preparing the three-dimensional composite aerogel phase change material according to claim 6, characterized in that: The particle size of the particles after ball milling in S13 is 100-150 μm, and the heating rate of the nitrogen is 3-5° C. / min.
9. The method for preparing the three-dimensional composite aerogel phase change material according to claim 6, characterized in that: The mass ratio of the oxidized honeycomb AlAg@C particles to polyethylene glycol in the S15 is 1:15-35, the molecular weight of the polyethylene glycol is 2000-8000, the heating reaction temperature is 90-120° C., and the time is 6-10 hours.